THE ROLE AND SIGNIFICANCE OF ANIMAL IMAGERY IN ENGLISH AND UZBEK FOLKTALES - Teshaboyeva (Scientific practical conference, 2025)
This article investigates the mythological, cultural, and literary importance of animal imagery—with special attention to the wolf—in both English and Uzbek folktales. Within Turkic mythology and Uzbek oral heritage, the wolf is honored as a sacred totem symbolizing bravery, protection, leadership, and spiritual strength. The research explores the mythic origins, folk rituals, linguistic representations, and narrative functions of the wolf by analyzing tales such as “The Hungry Wolf” and “The Lame Wolf.” It further compares the symbolic roles of the wolf in English and Uzbek traditions, revealing its dual nature as a guardian and a threat. Through comparative and typological analysis, the study illustrates how animal imagery embodies cultural morals, social values, and artistic expression. The results show that figures like the wolf possess not only poetic and folkloric relevance but also deep psychological and cultural resonance across different societies.